In Pursuit of Trophies : Analysis of English Football Club Owners’ Objectives - Laxa, Jan; Kotrba, Vojtěch; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2023)
This thesis develops a model framework for analysis of Premier League owners’ incentives and by applying a balanced panel dataset for 2020/2021 Premier League clubs between seasons 2001/2002 and 2020/2021 it approximates the value of the owners’ willingness to stay in the market despite recurring stated accounting losses. It operates with the clubs’ net valuation estimates calculated using data from clubs’ annual financial statements published by the Companies House, match statistics data from Livesport, player valuation estimates from Transfermarkt, Google Trends search popularity data, and other relevant economic time series for the United Kingdom. All monetary variables were expressed in real terms. Using Random effects panel data model, it finds significant explanatory variables for changes in clubs’ net valuations. Findings are then used to derive implications for year-on-year and total changes in owners’ utility during the selected timeframe. Thesis supports other literature as it finds that on average for Premier League as a whole, clubs do operate with respect to net valuation break-even constraint. However, on individual basis, clubs were found either increasing or decreasing their initial 2001/2002 net valuation. It was also found that clubs were operating on threshold for inversed parabolic relationship between total change in net valuation and total number of trophies won during the studied time, thus supporting the win-maximization assumption. Finally, 11 Premier League clubs have been found to provide an economic profit to their owners accounted for owners’ investment opportunity costs. For these owners, utility has been found to have increased regardless of other ownership benefits, thus the minimum value assigned to the non-monetary benefits of club ownership was set to zero.
For the rest, minimum non-zero value of all non-measurable non-monetary benefits coming from owning the club was calculated to satisfy the Austrian notion of demonstrated preferences.
Vedoucí práce: Vojtěch Kotrba
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses